2010
DOI: 10.1002/dmrr.1150
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of oral glucosamine use and effects on glucose metabolism in normal and diabetic individuals

Abstract: Glucosamine (GlcN) is a widely utilized dietary supplement that is used to promote joint health. Reports that oral GlcN supplementation at usual doses adversely affects glucose metabolism in subjects with impaired glucose tolerance have raised concerns that GlcN should be contraindicated in individuals with diabetes and those at risk for developing it. This review addresses its potential, when used at typical doses, to affect glucose metabolism and insulin sensitivity in healthy individuals and those with diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 56 publications
0
62
0
5
Order By: Relevance
“…Despite some studies suggesting similar effects in 425 humans, systematic reviews of clinical studies have identified limited evidence for an 426 effect of oral glucosamine on insulin sensitivity or glucose tolerance in human subjects, 427 but acknowledge the need for further study in subjects with existing risk of impaired 428 glucose metabolism (Anderson et al 2005;Dostrovosky et al 2011;Simon et al 2011). 429…”
Section: Discussion 325mentioning
confidence: 99%
“…Despite some studies suggesting similar effects in 425 humans, systematic reviews of clinical studies have identified limited evidence for an 426 effect of oral glucosamine on insulin sensitivity or glucose tolerance in human subjects, 427 but acknowledge the need for further study in subjects with existing risk of impaired 428 glucose metabolism (Anderson et al 2005;Dostrovosky et al 2011;Simon et al 2011). 429…”
Section: Discussion 325mentioning
confidence: 99%
“…This position has been endorsed by recent reviews on the topic [38-40]. But we do not want to ignore the few studies hypothesizing that glucosamine may affect glucose metabolism, at least in subjects with untreated diabetes or glucose intolerance [41, 42].…”
Section: Discussionmentioning
confidence: 95%
“…However, the role of one metabolite, glucosamine, in T2D in humans is unclear. Glucosamine infusion in nondiabetic rats decreases insulin-mediated glucose uptake and glycogen synthesis in skeletal muscle [34], but glucosamine has shown no effect on insulin-mediated metabolism in humans [35]. …”
Section: Discussionmentioning
confidence: 99%